1998
DOI: 10.1016/s0008-6363(97)00271-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of reverse-mode sodium–calcium exchange to contractions in failing human left ventricular myocytes

Abstract: The increases in phasic contraction magnitude observed in high-Na cells compared to Na-free cells were most likely due to increased SR Ca loading resulting from increased reverse-mode Na-Ca exchange. Our results also suggest that tonic contractions in high-Na cells were mediated by Ca entry via reverse-mode Na-Ca exchange and were not the result of either SR Ca release or L-type Ca channel activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 25 publications
1
37
0
3
Order By: Relevance
“…(9), using 31 P NMR in the same transgenic model, reported comparable decreases in myocardial ATP levels and pH during ischemia in wild-type and transgenic hearts. Accordingly, our data suggest that reduced diastolic Ca i 2ϩ and preserved peak Ca i 2ϩ during ischemia in transgenic hearts were a consequence of a greater abundance of Na ϩ /Ca 2ϩ exchangers operating in the forward mode and the reverse mode.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…(9), using 31 P NMR in the same transgenic model, reported comparable decreases in myocardial ATP levels and pH during ischemia in wild-type and transgenic hearts. Accordingly, our data suggest that reduced diastolic Ca i 2ϩ and preserved peak Ca i 2ϩ during ischemia in transgenic hearts were a consequence of a greater abundance of Na ϩ /Ca 2ϩ exchangers operating in the forward mode and the reverse mode.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies (5,17,34,39,43) have demonstrated downregulation of SR function in the failing heart that may, in part, contribute to alterations in Ca i 2ϩ , reduced tension development, and a blunted force-frequency relation in heart failure (8,12,18,40). Gene expression of the cardiac Na ϩ /Ca 2ϩ exchanger, however, is enhanced in failing human hearts (10,43), perhaps as a compensatory adaptation to assist impaired SR Ca i 2ϩ resequesteration during relaxation (10,39,43) or to boost inotropy by increasing Ca i 2ϩ influx during the action potential (10,27,31,43). Data from a recent study in dogs (39) indicate that a greater fraction of Ca i 2ϩ removal is attributable to Na ϩ /Ca 2ϩ exchange than to SR uptake in failing myocytes.…”
Section: /Camentioning
confidence: 99%
“…NCX is known to play a critical role in the mainte- nance of Ca 2ϩ homeostasis in cardiomyocytes (39 -40) and thus in the modulation of cardiac contractility. It has been shown that NCX activity is altered during cardiac remodeling in the hypertrophic heart and during heart failure (7,41). The hearts from CKM and sMiCK double knock-out mice have been demonstrated to show increased sensitivity to ischemia- reperfusion injury and show a greater increase in diastolic Ca 2ϩ concentration during ischemia (42); therefore the interaction between NCX1 and CKs may be important to prolonging normal heart functioning when a pathological condition such as ischemia starts to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Ca 2ϩ influx via the exchanger, contributing to Ca 2ϩ loading of the SR, was recently described in the rabbit heart after myocardial infarction. 28 In human heart failure, the Na/Ca exchanger also appears to be very important in determining the SR Ca 2ϩ load, 29 a notion supported by the finding that increasing Na ϩ influx enhances contractile function to a larger extent in myocardium from heart failure patients than from controls. 30 Increased exchanger activity has been reported for some animal models of hypertrophy 31 and heart failure, 32 but not all, 10,33 suggesting that eventual changes, as in the dog with CAVB, represent a specific response associated with a particular type of Ca 2ϩ handling.…”
Section: Perspectivesmentioning
confidence: 98%